Ustawodawstwo karne w kodyfikacji płockiej biskupa Jakuba z Korzkwi (1396-1425) - Herod, Patrycja E. (Archiwa, Biblioteki i Muzea Kościelne, 2020)
This article presents the person of Bishop of Plock Jakub from Korzkiew, the arms-bearing Syrokomla, a distinguished author of Plock codifi cation. It shows his work in the Roman Curia, the service for his country, the relationship with the Teutonic Order, his characteristics as an administrator and pastor of the diocese entrusted to him. Then the author focuses entirely on the synodical statutes of Plock announced on January 26, 1423 by Jakub. The synods which are discussed refer to the bishopric, the stages of establishing the Plock Code and the characteristic of the particular regulations. The whole text is crowned by a presentation of various punitive measures adopted by the legislator in this classic of Polish medieval canon law.